From drills to clil: the paradigmatic and methodological evolution towards the integration of content and foreign language (2014)
Content and language integrated learning has become a common practice in European higher education. In this paper, I aim to describe how this integrated teaching practice comes as a result of a paradigmatic and pedagogical evolution. For this purpose, the main linguistic paradigms will be revisited diachronically, followed by a revision of the main pedagogical trends in teaching English as a second language. This theoretical overview culminates in a predominantly constructivist practice that is more pragmatic and contextualized than ever before. From a language teacher’s standpoint and in language university classrooms, content and language integrated learning comes to solve the forever present decontextualization.El aprendizaje integrado de contenidos y lengua extranjera se ha convertido en práctica común en la educación superior europea. En este artículo se describe cómo esta práctica de enseñanza integrada surge como resultado de una evolución paradigmática y pedagógica. Con ese fin, se revisan diacrónicamente los distintos paradigmas lingüísticos, seguidos de una descripción de los métodos pedagógicos en la enseñanza del inglés como segunda lengua. Este recorrido teórico culmina en una práctica constructivista predominante que es más pragmática y contextualizada que ninguna otra usada con anterioridad. Desde la perspectiva del profesorado de idiomas y dentro de un aula de idiomas universitaria, el aprendizaje integrado de contenidos y lengua extranjera ofrece la solución al problema constante de la descontextualización.